Marketing Strategy In Improving Purchase Decisions In Syifa Hydroponic Farming Business In Medan City - Sitorus, Vira Rezkika; Effendi, Ihsan; Rafiki, Ahmad (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze marketing strategies in hydroponic farming businesses, focusing on the impact of price, social media, attitudes, and subjective norms on purchasing decisions, with purchase intention serving as an intervening variable. Grounded in the Theory of Reasoned Action (TRA), the research employs a quantitative methodology, utilizing Structural Equation Modeling Partial Least Square (SEM-PLS) for data analysis. The study was conducted at Syifa Hidroponik, a hydroponic company located in Medan, Indonesia. A Simple Random Sampling technique was used to select 109 participants. The findings reveal that price positively influences purchase intention, suggesting that consumers are more inclined to buy when they perceive the pricing as favorable. This aligns with previous research indicating that competitive pricing can enhance purchase intentions. Social media also exerts a positive effect on purchase intention, highlighting the role of platforms like Instagram and Facebook in shaping consumer behavior. This is consistent with studies demonstrating the effectiveness of social media in promoting products and engaging customers. Attitude and subjective norms were found to positively influence purchase intention as well, indicating that personal beliefs and perceived social pressures significantly impact consumers' intentions to purchase hydroponic products. Finally, purchase intention positively affects actual purchasing decisions, confirming the mediating role of purchase intention in the relationship between the studied variables and purchasing behavior. These insights suggest that hydroponic businesses should consider competitive pricing strategies and leverage social media platforms to enhance consumer attitudes and align with societal norms, thereby boosting purchase intentions and actual sales.